CFD based Hydrodynamic Parametric study of inclined injected Supersonic steam into subcooled water - Khan, A.; Sanaullah, K.; Takriff, M.S; Hushairi, Zen; Lim, Soh Fong; Ajmal, Shah (Research Publishing., 2014)
Hydrodynamic parametric study of the supersonic steam injection into subcooled water is investigated.The phenomenon of direct-contact condensation, used in steam driven jet injectors, nuclear reactor emergency core cooling systems and direct-contact heat exchangers was investigated computationally by injecting an inclined steam jet without the presence of non condensable gases using a supersonic nozzle submerged in subcooled water. Ansys Fluent based Euler-Euler multiphase model is used. The angle of inclination is varied from 450 to 00 with a decrement of 200 for each computation with the constant inlet pressure of 7 bars and water temperature of 300C. It was found that the temperature and pressure near the nozzle exit showing an abrupt height with the instantaneous condensation upon venting. The hydrodynamic Gaussian profile width is more in the case of vertical injection as compare to the inclined injection which depict the effect of static water fluid pressure and gravity on pressure head and temperature.